Constraining Future Antarctic Warming Under Five Different Emissions Scenarios in the CMIP6 Multi‐Models - Yuqi Sun; Yulun Zhang; Yetang Wang; Petra Heil; Shugui Hou; Zhaosheng Zhai (Geophysical Research Letters)
Abstract The Coupled Model Inter‐comparison Project Phase 6 (CMIP6) multi‐models predict future warming over Antarctica under five different scenarios, but their uncertainties remain high and have not been well constrained. Here we find that the projected Antarctic warming robustly correlates with simulated averaged temperature trends during 1958–2012 across the CMIP6 multi‐models under each scenario, which is thereby used to refine future air temperature projections using observation‐based temperature reconstruction. The median of future warming projections under the five scenarios reduces by 24%, 19%, 18%, 21%, and 21%, respectively. The constrained uncertainty ranges are narrowed down, with the likely range by the end of the century relative to 1850–1900 baseline declining from 4.2°C–6.8°C to 3.2°C–6.1°C under the highest emission scenario. The application of ERA5 for the same constraint shows an increase in future warming and constrained uncertainty ranges. This suggests a key role of observational data set uncertainties in the performance of emergent constraints.